ANALISIS PERLAKUAN AKUNTANSI ASET BIOLOGIS BERDASARKAN INTERNATIONAL ACCOUNTING STANDARD 41 PADA PT. PERKEBUNAN NUSANTARA VII (PERSERO) - Farida, Ike (Jurnal Akuntansi AKUNESA, 2013)
The purpose of this research is to know implementation of Accounting Standard about biological asset. The research method used in this research is research about data annual report on the one of plantation corporate called PTPN VII is located in Bandar Lampung. The implementation process is conducted based on the compatibility about recognition, measurement, and reporting, of biological asset?s PTPN VII. Research of data in order to know about their activity in the biological asset processing. Some appropriate unsure with International Accounting Standard (IAS) are recognition of Unaffordable Plants and Affordable Plants and the use of fair value  method as a measurement basis of this asset. This means that PTPN VII has to do some suggestions in biological asset reporting offered by researcher for the better implementation about IAS and in order to increase the quality of their financial report.   Keywords: International accounting standard, biological asset, financial reporting.